A Cr(iii) supramolecular network composite membrane with high water stability and proton conductivity. Issue 13 (15th March 2023) - Zhou, Shu-Fang; Zhang, Hong-Jie; Zhang, Chen-Xi; Wang, Qing-Lun
Abstract : The blending matrix membrane with highly efficient double proton conduction pathways has been synthesized. The value of 1 @CS/PVP-10 is ten times higher than that of 1 . Abstract : Proton exchange membranes have attracted considerable attention as the core component of fuel cells. Among them, the blending matrix membrane will result in a composite membrane with the advantages of individual components. Chitosan (CS) has a strong binding capacity to Cr 3+ ions, and it combines with polyvinylpyrrolidone (PVP) to form a rich network of hydrogen bonds. Hence, the composite membrane of blending hydrophilic polymer CS-PVP matrix and metal-hydrogen-organic frameworks (MHOFs) [Cr2 (DBPZ)2 (μ-OH)2 ] 1 (H2 DBPZ) = bis(3, 5-dicarboxypyrazol-1-yl)dicarboxylic acid were fabricated. The Cr 3+ ion is six-coordinated by four oxygen atoms and two nitrogen atoms to form an octahedron configuration. Two DBPZ 2− ligands connected two Cr 3+ ions forming a dimeric unit, and an adjacent dimeric core are further connected by a hydrogen bond to form a 3D supramolecular framework. The proton conductivity of 1 @CS/PVP-10 reached up to 8.64 × 10 −2 S cm −1 at 363 K and 98% RH, which is about 10 times higher than that of 1 .